2004
DOI: 10.1172/jci200421804
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic nucleotide phosphodiesterase 3A–deficient mice as a model of female infertility

Abstract: Since cAMP blocks meiotic maturation of mammalian and amphibian oocytes in vitro and cyclic nucleotide phosphodiesterase 3A (PDE3A) is primarily responsible for oocyte cAMP hydrolysis, we generated PDE3A-deficient mice by homologous recombination. The Pde3a -/-females were viable and ovulated a normal number of oocytes but were completely infertile, because ovulated oocytes were arrested at the germinal vesicle stage and, therefore, could not be fertilized. Pde3a -/-oocytes lacked cAMP-specific PDE activity, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 48 publications
6
74
0
2
Order By: Relevance
“…Oocytes, cumulus-oocyte complexes (COCs), and POFs were collected as previously described [12]. The Pde3a À/À colony (C57BL/63129Sv), generated as previously described [26], was established and maintained through heterozygous breeding. Mice were genotyped by PCR using specific primers designed to detect WT and targeted alleles from extracted tail DNA as previously described [26].…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oocytes, cumulus-oocyte complexes (COCs), and POFs were collected as previously described [12]. The Pde3a À/À colony (C57BL/63129Sv), generated as previously described [26], was established and maintained through heterozygous breeding. Mice were genotyped by PCR using specific primers designed to detect WT and targeted alleles from extracted tail DNA as previously described [26].…”
Section: Animalsmentioning
confidence: 99%
“…We have recently reported that phosphodiesterase type 3A (PDE3A) is required for resumption of meiosis in mammalian oocytes and that females lacking PDE3A are infertile [26]. The possibility that PDE3A could be regulated by cGMP in the oocyte [27], as well as the data suggesting a role for cGMP in oocyte meiotic resumption, prompted us to further investigate the interplay between ovarian cGMP homeostasis, PDE3A, and oocyte meiotic resumption.…”
Section: Introductionmentioning
confidence: 99%
“…In the mouse, activation of EGFR is involved in LH-induced decrease in cGMP transport from granulosa and cumulus cells to the oocyte and both EGFR and MAPK3/1 activities participate in gap junction closure (Vaccari et al 2009, Norris et al 2009, Hsieh et al 2011. These mechanisms contribute to relieve meiotic block as cGMP works in oocytes as a natural inhibitor of phosphodiesterase 3A, maintaining high intracellular level of cAMP and meiotic arrest of the oocyte (Masciarelli et al 2004). In the pig, activation of MAPK3/1 in cumulus cells is also a prerequisite for gonadotropin-stimulated resumption of meiosis (Meinecke & Krischek 2003, Liang et al 2005.…”
Section: Signaling In Pig Cumulus-oocyte Complexesmentioning
confidence: 99%
“…cAMP is produced in the oocyte through the constitutive action of an oolemmal G protein-coupled receptor (GPR3 in mouse) that stimulates G protein (Gs) to activate adenylyl cyclase (Hinckley, Vaccari, Horner, Chen, & Conti, 2005;Horner et al, 2003;Mehlmann, Jones, & Jaffe, 2002;Mehlmann et al, 2004;Norris et al, 2007). Importantly, the oocyte also possesses the capacity to hydrolyse cAMP through the action of phosphodiesterases, specifically PDE3A (Masciarelli et al, 2004). Although the cumulus cells of the follicle also produce cAMP that can be transferred via transzonal gap junctions (Bornslaeger & Schultz, 1985;Dekel, Lawrence, Gilula, & Beers, 1981), studies using the PDE3 and GPR3 knockout mice revealed that oocyte mediated regulation of cAMP is sufficient and necessary for meiotic reentry (Hinckley et al, 2005;Ledent et al, 2005;Mehlmann et al, 2004).…”
Section: Introductionmentioning
confidence: 99%